Village Cinemas Recoleta (2003)
Complejo multicine con 11 plantas y un amplio frente comercial gastronómico.
Keywords: ARGENTINA; BUENOS AIRES; SALAS DE ESPECTACULOS; CINES; BODAS, MARTÍN; MIANI, RODOLFO; ANGER, ALEJANDRO; ARQUITECTURA CORPORATIVA